EVALUATION OF VARIABLE INTENSITY OF HEAT REMOVAL FROM THE SURFACE OF FALLING AND CRYSTALLIZING MELT DROPLETS IN THE PROCESS OF THEIR PRILLING - E. N. Zvereva; Yu. A. Taran (Тонкие химические технологии)
The method of calculation of the intensity of heat removal from the surface of the crystallizing melt droplets is presented. A comparison with the experimental fixed values representing the intensity of the heat transfer between the surface of the resulting pellet and cooling agent is carried out. The influence of heat transfer coefficient on the surface of the pellet changes on complete crystallization time, and therefore on the size of the granulation tower, is analyzed. Conditions defining the heat transfer between the granule surface and surrounding coolant, while full crystallization in conjunction with the dependence of the rate of nucleation and growth of the granules determine mechanical properties of ammonia fertilizer granules.